Novel treatment technologies for PFAS compounds: A critical review - Kucharzyk, Katarzyna H.; Darlington, Ramona; Benotti, Mark; Deeb, Rula; Hawley, Elisabeth (Journal of environmental management, 2017)
Perfluorinated compounds such as perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) have recently drawn great attention due to their wide distribution in aquatic environments. The understanding of the physicochemical properties and fate and transport of PFAs in groundwater is still limited. Preliminary studies indicate that these compounds can readily bioaccumulate and pose human and animal health concerns. Due to their physicochemical properties, PFOS and PFOA are water soluble, nonvolatile and persistent in the environment, which is a cause of concern related to their treatment with conventional remediation technologies. Extraction with inefficient carbon adsorption is one of the most common treatment technologies for remediation of PFOS- or PFOA-impacted groundwater. Several other innovative and promising technologies, including sonochemistry, bioremediation and photolysis, have been tested for their effectiveness in removal of perfluorinated compounds. This paper provides a baseline for understanding research needs to better develop treatment technologies for PFOA and PFOS in groundwater. Frontiers for improving the state of practice for PFOA and PFOS treatment include the development of more cost-effective ex situ treatment methods and the development and demonstration of promising in situ treatment technologies at the pilot and full scale. [Display omitted] •This paper provides a review of treatment of perfluorinated compounds.•In situ and ex situ methods for removal of perfluorinated compounds are discussed.•This review discusses research needs for treatment of contaminants.•Knowledge gaps on cleanup technologies are listed within the review.